A taxonomic revision of Boiga multomaculata (Boie, 1827) and B. ochracea (Theobald, 1868), with the description of a new subspecies (Squamata, Serpentes, Colubridae) - Köhler, Gunther; Charunrochana, Panupong Thammachoti; Mogk, Linda; Than, Ni Lar; Kurniawan, Nia; Kadafi, Ahmad Muammar; Das, Abhijit; Tillack, Frank; O’shea, Mark (Zootaxa, 2023)
The analyses of molecular genetic data (mtDNA markers 16S, ND4, CYTB, and the nuclear marker c-mos) provided evidence that the Asian cat snake taxa Boiga multomaculata and B. ochracea actually represent a single species. They form mixed clades of low intraclade genetic differentiation. This evidence for conspecificy is supported by the lack of differentiation in all examined pholidotic and morphometric characters. Therefore, we formally place Dipsas ochracea Theobald, 1868 in the synonymy of Dipsas multomaculata Boie, 1827. We provide a summary of the tangled taxonomic history of the taxa involved in this study. Also, we resurrect Dipsadomorphus stoliczkae Wall, 1909 from synonymy of B. ochracea, for specimens exhibiting 21 midbody dorsal scale rows. Boiga stoliczkae is found in the Himalayas north and west of the Brahmaputra valley. Finally, based on the detection of historical genetic lineages within the newly defined species Boiga multomaculata we recognize three subspecies: Boiga multomaculata multomaculata (Boie, 1827), Boiga multomaculata ochracea (Theobald, 1868), and Boiga multomaculata septentrionalis n. ssp. which is distributed in northern Myanmar and Assam and Nagaland, India. We designate BMNH 1946.1.2.60 (1) as neotype of Dipsas ochracea Theobald, (2) as lectotype of D. ochraceus Günther, and (3) as lectotype of Boiga ochracea walli Smith, thereby making these names objective synonyms. Finally, we designate BMNH 94.12.31.55 as lectotype of Dipsadomorphus stoliczkae Wall.